Evaluation of E-Learning Practices in Undergraduate Medical Education: Results of a Survey in Sri Lanka - Edirippulige, Sisira; Marasinghe, Rohana B.; Smith, Anthony C.; Fujisawa, Yoshikazu; Herath, Walisundara B.; Jiffry, M. T. M.; Wootton, Richard (My University, 2013)
Objective: The present study investigates the knowledge, perceptions and the utilisation of e-learning modalities in medical education by the students in Sri Lanka. We also examined the potential barriers which may prevent the uptake of e-learning strategies in health and medical education. Methods: A questionnaire focusing on the knowledge, attitudes and expectations of medical students towards e-learning was distributed to all final year medical students (n=136) at the Faculty of Medicine, Sri Jayewardenepura University, Sri Lanka. The survey was conducted during their regular lectures and completed questionnaires were collected after their classes. Findings: 100 surveys (74%) were completed and returned. Nearly half of the respondents (43%) admitted that they were familiar with the term e-learning. Only 19% of respondents stated that they had used e-learning modalities for educational purposes. The majority of respondents said that they had not used web-based learning material or multimedia resources for medical education. However, more than half of (56%) respondents agreed that e-learning modalities would be useful tools in medical education and 49% said that e-learning must be expanded in medical education. Conclusions: Despite the majority of respondents believed that e-learning modalities can be a useful tool to address some of the problems in medical education in developing countries, a lack of technology and learning opportunities have restricted the potential benefits.